Guided vs. conventional anti-platelet therapy for patients with acute coronary syndrome: A meta-analysis of randomized controlled trials - Zhong, Peng-Yu; Deng, Jian-Ping; Zhao, Jing-Hong; Peng, Lei; Liu, Tao; Wang, Hao-Yu (Frontiers in Cardiovascular Medicine, 2023)
Background: Whether guided antiplatelet therapy in patients with acute coronary syndrome (ACS) is effective in improving net clinical benefits compared with conventional antiplatelet therapy remains controversial. Therefore, we assessed the safety and efficacy of guided antiplatelet therapy in patients with ACS and undergoing percutaneous coronary intervention. Method: We retrieved PubMed, EMBASE and Cochrane Library databases to select the relevant randomized controlled trials comparing the guided and conventional antiplatelet therapy in patients with ACS. The primary and safety outcomes are major adverse cardiovascular events (MACE) and major bleeding, respectively. The efficacy outcomes included myocardial infarction, stent thrombosis, all-cause death and cardiovascular death. We selected the relative risk (RR) and 95% confidence intervals as effect size and calculated it in the Review Manager software. In addition, we evaluated the final results by trials sequential analysis. (Registered by PROSPERO, CRD 42020210912) Results: We selected seven randomized controlled trials and included 8451 patients in this meta-analysis. Guided antiplatelet therapy can significantly reduce the risk of MACE(RR 0.64, 0.54-0.76, P<0.00001), myocardial infarction (RR 0.62, 0.49-0.79, P=0.0001), all-cause death(RR 0.61, 0.44-0.85, P=0.003) and cardiovascular death (RR 0.66, 0.49-0.90, P=0.009). In addition, there is no significant difference between the two groups in stent thrombosis (RR 0.67, 0.44-1.03, P=0.07) and major bleeding (RR 0.86, 0.65-1.13, P=0.27). The subgroup analysis showed that the guided group based on genotype tests could bring benefits in MACE and myocardial infarction. Conclusions: The guided antiplatelet therapy is not only associated with a comparable risk of bleeding, but also with a lower risk of MACE, myocardial infarction, all-cause death, cardiovascular death and stent thrombosis than conventional strategy in patients with ACS.